Effect of direct fed anaerobic fungal culture on rumen fermentation, nutrient utilization and live weight gain in crossbred heifers - SAMANTAI, A K; SINGH, K K; DAS, M M; PAILAN, G H (The Indian Journal of Animal Sciences, 2011)
Attempts were made to evaluate the potential gut anaerobic fungi as probiotic in crossbred heifers. Crossbred heifers (10) were randomly divided into equal group 0 1 and G2â€¢ All the experimental heifers were offered ad lib. wheat straw and concentrate mixture (containing mustard cake 35, barley 25, wheat bran 38, mineral mixture 1 and common salt 1 %) @ 1% of body weigh. In addition to that, 2 ml of 4 days old Pirmyces sp. (an isolate of goat mInen) was offered to heifers of O2 2 ml of same fungal media was ven to the heifers of G1 to neutralize the effect of media. The exp.eriment lasted for 90 days. At the middle of experiment, rumen liquor was collected to monitor the rumen metabolItes and nlicrobial population. A digestibility trial was also conducted to see the effect of probiotic on dry-matter intake and nutrient utilization. The rumen pH, total VFAs ammonia N and total N were not affected by the daily administration of anaerobic fungal probiotic. The population of total viable bacteria was 25.5xl08 and 26.5xl08 ImI, fungi was 3.65xl03 and 9.l5xl03 Iml in G1 and O2, respectively. Similarly, the protozoa population was 9.24xI05 and 10.23xl05 Iml in 0 1 and G2, respectively, which was also unaffected by the inclusion of fungal probiotic. The dry-matter intake as % of body weigh was similar in 2 groups. Nutrient digestibility although were numerically higher in probiotic fed heifers still did not differ significantly. The average live weight gain in G1 was 498 g/head/day, while it was 513 g/headJday in 02 indicating no positive response of anaerobic fungal probiotic. Â